Tuning the Fe–N4 sites by introducing Bi–O bonds in a Fe–N–C system for promoting the oxygen reduction reaction. Issue 2 (13th December 2021) - Jin, Huihui; Zhu, Jiawei; Yu, Ruohan; Li, Wenqiang; Ji, Pengxia; Liang, Lvhan; Liu, Bingshuai; Hu, Chenxi; He, Daping; Mu, Shichun
Abstract : The Bi–O bonding near the Fe–N site regulates and endows the Fe electronic structure with a lower band gap, which promotes the oxygen reduction activity of the Fe–N site, and provides a new direction for the optimization of metal–N–C catalysts. Abstract : Elemental Bi is effective in optimizing the electrocatalytic activity of perovskite oxides and noble metals, but has never been used to adjust the oxygen reduction activity of Fe/N–C catalysts. Here, in order to introduce the Bi element into the Fe/N–C system with atomic-level dispersion, by means of a rod-like C3 N4 template carrying Fe and Bi atoms as a sacrificial agent, we successfully dope Bi atoms into the ZIF-8 derived Fe/N–C carbon system with a porous rod-like structure in the form of Bi–O (Fe/Bi-RNC). Mössbauer spectroscopy and electron paramagnetic resonance tests prove that Bi doping leads to the formation of higher active Fe–N sites in Fe/Bi-RNC. The oxygen reduction reaction (ORR) of the as-prepared Fe/Bi-RNC is highly superior to the catalyst without Bi doping (Fe-RNC) in both alkaline and acidic electrolytes. The density functional theory (DFT) calculation results further unveil that the existence of the Bi–O bond reduces the band gap of Fe–N4, and their cooperation is very favorable for electron transfer in the ORR rate-determining step, thereby triggering excellent oxygen reduction performance. These findings demonstrate that Bi atoms have a facilitating role in Fe/N–C oxygen reduction catalysts.